ANALYSIS OF THE ACTIVITIES OF EDO STATE AGRICULTURAL DEVELOPMENT PROGRAM EXTENSION SERVICES AMONG SMALL-SCALE CASSAVA FARMERS - Ehilenboadiaye, C. O.; Onemolease, E. A.; Omoregie, O. (FUDMA Journal of Sciences, 2021)
This study assessed the expectations of cassava tuber farmers from the agricultural extension service providers in Edo State, Nigeria. It examined the support presently given to cassava farmers by the extension service viz-a-viz the needs of the farmers. To achieve these objectives, data were collected from 196 cassava tuber producers, randomly sampled from the three agricultural zones in the State. Data were analysed using descriptive and inferential (multiple regression, Friedman and Cochran tests) statistics. Cochran test (Ï‡2 = 596.35; p<0.01) revealed that information delivery on available improved varieties (0.939), land clearing/preparation methods (0.878), cassava stem treatment (0.872), recommended planting distance/spacing (0.867) and fertilizer application methods (0.857) were significant areas in which farmers have been supported by the extension service. Friedman test results (Ï‡2 = 135.52; p<0.05) revealed that linking farmers to input suppliers (mean rank = 9.17) and training on proper cutting of cassava stems (mean = 9.10) were among the most significant needs. Multiple regression revealed that farm size (p<0.05) was the only variable significantly correlated with the extension needs of the farmers. The major constraints facing cassava tuber producers included high cost of improved varieties (mean = 3.85) and farming inputs (mean = 3.82) as well as poor access roads for transportation of cassava tubers. Taking advantage of group formation and linkage to credit were recommended.